2009
DOI: 10.1111/j.1365-2966.2009.14743.x
|View full text |Cite
|
Sign up to set email alerts
|

The global gas and dust budget of the Large Magellanic Cloud: AGB stars and supernovae, and the impact on the ISM evolution

Abstract: We report on an analysis of the gas and dust budget in the interstellar medium (ISM) of the Large Magellanic Cloud (LMC). Recent observations from the Spitzer Space Telescope enable us to study the mid‐infrared dust excess of asymptotic giant branch (AGB) stars in the LMC. This is the first time we can quantitatively assess the gas and dust input from AGB stars over a complete galaxy, fully based on observations. The integrated mass‐loss rate over all intermediate and high mass‐loss rate carbon‐rich AGB candid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
269
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 202 publications
(290 citation statements)
references
References 181 publications
(310 reference statements)
17
269
4
Order By: Relevance
“…Carbon stars show a band attributed to SiC at 11.3 μm, in addition to amorphous carbon dust, which has continuous emission without a characteristic feature in the infrared and which dominates dust mass and infrared excess in carbon stars (Groenewegen et al 1995). Carbon stars with a higher mass-loss rate become red, owing to amorphous carbon dust (Matsuura et al 2009). The SiC feature falls in the S 9W-band (see Fig.…”
Section: (S9w -L18w) Vs (J -L18w)mentioning
confidence: 99%
“…Carbon stars show a band attributed to SiC at 11.3 μm, in addition to amorphous carbon dust, which has continuous emission without a characteristic feature in the infrared and which dominates dust mass and infrared excess in carbon stars (Groenewegen et al 1995). Carbon stars with a higher mass-loss rate become red, owing to amorphous carbon dust (Matsuura et al 2009). The SiC feature falls in the S 9W-band (see Fig.…”
Section: (S9w -L18w) Vs (J -L18w)mentioning
confidence: 99%
“…The astronomical evidence for the synthesis of dust in AGBs is brought by the identification of typical dust features in the spectral energy distribution (SED) of AGB stars, including the 9.7 µm and 18 µm features of silicates in oxygen-rich AGBs and the 11.3 µm feature ascribed to silicon carbide grains in carbon stars. Recent surveys with the Herschel space telescope of the Magellanic Clouds have questioned the primacy of AGBs as galactic dust providers at lower metallicity than that of the Milky Way (Matsuura et al 2009;Boyer et al 2012). However, owing to their large number in stellar populations, AGB stars remain important dust producers in the local and high redshift universe.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Matsuura et al (2009) and Matsuura, Woods & Owen (2013) showed that enrichment of the ISM by AGB stars in the LMC and SMC fails to explain the total dust and PAH abundance in these galaxies. PAH destruction in the ISM is apparently so effective (Micelotta, Jones & Tielens 2010a) that they do not survive the travel from parent stars to H ii complexes where they are observed.…”
Section: Introductionmentioning
confidence: 99%